2012
DOI: 10.1103/physrevb.85.104106
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the SiNx/TiN(001) interface

Abstract: The structure of the SiN x tissue phase in superhard TiN/SiN x nanocomposites has been debated in the literature. We present a theoretical investigation of the possibility of crystalline and coherent (001) interfaces that satisfies the two necessary criteria, stability with respect to lattice vibrations as well as to variations in stoichiometry. It is found that one monolayer of Si tetrahedrally coordinated by N in a B3-like geometry embedded between B1-TiN(001) surfaces is both dynamically stable and thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Analytical scanning transmission electron microscopy with energy dispersive spectroscopy and x-ray diffraction (XRD) were used for microstructure characterization and nanoindentation for mechanical property determination of asdeposited and annealed coatings. [6][7][8][9] At the same time, ab initio computer simulations in the framework of density functional theory (DFT) have become increasingly important for the interpretation of the experimental information, 11,12 predictions of materials properties, [13][14][15][16][17][18][19][20] and for the knowledge-based materials design. 4 The accuracy and reliability of theoretical calculations have substantially increased, to the extent that in the absence of corresponding experimental information, or in cases when it is limited, computed properties have become accepted by the research community almost at the same level of trust as measured data.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical scanning transmission electron microscopy with energy dispersive spectroscopy and x-ray diffraction (XRD) were used for microstructure characterization and nanoindentation for mechanical property determination of asdeposited and annealed coatings. [6][7][8][9] At the same time, ab initio computer simulations in the framework of density functional theory (DFT) have become increasingly important for the interpretation of the experimental information, 11,12 predictions of materials properties, [13][14][15][16][17][18][19][20] and for the knowledge-based materials design. 4 The accuracy and reliability of theoretical calculations have substantially increased, to the extent that in the absence of corresponding experimental information, or in cases when it is limited, computed properties have become accepted by the research community almost at the same level of trust as measured data.…”
Section: Introductionmentioning
confidence: 99%
“…Taking Si vacancies into consideration is known to stabilize the interface in TiN/SiN system. 8,23 However, our calculations with 3:4 SiN stoichiometry also showed the behavior for the interface stability that was similar to the one obtained with 1:1 stoichiometry. Namely, it was found that the (001) interface relaxed easily into a stable configuration, see Fig.…”
Section: © 2014 Author(s) All Article Content Except Where Otherwismentioning
confidence: 56%
“…7 Using the (1×1) supercell we found that the Si-atoms in the (001) interface are highly unstable in the ideal B1 position, similar to the TiN/SiN (001) case. 5,6,23 The Si-atom after full relaxation moved within the (x-y)-plane a distance of 14% of the cell size. The same amount of Si relaxation, though with a more complex but still regular pattern, was obtained by using (2×2) in-plane supercell.…”
Section: © 2014 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…A cubic structure that would satisfy that is the zinc blende, B3, structure shown in Figure 2.1 b). However, the results from Paper 1 show that the measurements, when compared to simulations and calculations, indicate a B1 like structure for the SiNx challenging the more stable bonding geometry (B3) for bulk material [23].…”
Section: B) A)mentioning
confidence: 97%